The right to be heard: Australian children's views about their involvement in decision-making following parental separation - Campbell, Alan (2008)
This article describes the findings from a qualitative study that explored the views of a small group of Australian children about their involvement in decision-making processes following their parents' separation. Sixteen children, aged between seven and 17 years, participated in in-depth interviews that focused on their understandings of the rights of children in decision-making, their descriptions of how decisions about their future were made following their parents' separation, and their views on their own participation in decisions that directly affected them. Findings indicated that children need information from their parents about what is happening at the time of separation. Children expressed a belief that their opinions should be respected and acted upon, but that final decisions about children following separation should be made by parents. Additionally, the children in this study recognised the importance of members of the extended family in helping separated families to reach important decisions about their children. While this study involved a very small sample, these findings reflect those of other studies in the United Kingdom and New Zealand and underscore the importance for children of being included in the experience of family separation rather than having parents attempt to "protect" them. The findings suggest that such inclusion will ensure that children's best interests are the central focus of decisions made about them.